1990
DOI: 10.1111/j.1365-2044.1990.tb14880.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double‐blind study of interpleural analgesia after cholecystectomy

Abstract: Summary Continuous interpleural analgesia provided by 4 hourly injectionsPain relief after unilateral thoraco-abdominal operations may be provided by the administration of bupivacaine into the pleural space.'" A duration up to 27 hours after a single injection of 0.5% bupivacaine 20 ml with adrenaline 5 pg/ml has been reported,l but recent studies suggest that analgesia is usually shorter-lived.4.s In our experience, analgesia invariably wears off within 5 hours of administration of the above dose, although 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…Numerous studies demonstrate an acceptable safety profile with bupivacaine administered via the interpleural route [6, 8, 12–14, 16, 19]. In our study we used a conservative dosing regime and found no reported symptoms consistent with local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Numerous studies demonstrate an acceptable safety profile with bupivacaine administered via the interpleural route [6, 8, 12–14, 16, 19]. In our study we used a conservative dosing regime and found no reported symptoms consistent with local anaesthetic toxicity.…”
Section: Discussionmentioning
confidence: 66%
“…Whilst there are sufficient patients to detect a clinically important difference in the primary endpoint, we are unable to detect the true incidence of complications from interpleural analgesia due to the relatively small sample size. Plasma levo‐bupivacaine levels were not evaluated as they have been well reported in numerous other studies [1, 6, 8, 12, 13, 16, 19, 26]. Although we found no reported symptoms of local anaesthetic toxicity, it is possible that plasma levels may have demonstrated concentrations above the accepted safe range.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interpleural block has been most extensively studied for postoperative analgesia in patients undergoing unilateral subcostal and flank incisions, i.e. open cholecystectomy [1][2][3][4][5][6][7][8][9][10][11], renal surgery [1,[12][13][14] and unilateral breast surgery [1,12,15,16]. The dosing regimens used have been dealt with in our first review [17].…”
Section: Gall Bladder and Livermentioning
confidence: 99%
“…Tumour invasion of the brachial plexus [68] Unilateral breast surgery [1,12,15,16] Open cholecystectomy [1][2][3][4][5][6][7][8][9][10][11] Pain of acute herpes zoster and post herpetic neuralgia [64][65][66][67] Needle localisation and breast biopsysole anaesthetic [15] Laparoscopic cholecystectomy [25,26] Chronic regional pain syndromes of the upper limb [36,61,63] Thoracotomy [42,43,45,[48][49][50][51] Renal surgery [1,[12][13][14] Upper limb ischaemia [62] Chest drain [108,109] Abdominal surgery (bilateral blocks) [55,56] Cardiac surgery [53,54] Percutaneous hepatic and biliary drainage procedures [27][28][29] Thoracic sympathectomy…”
Section: Head Neck and Upper Extremity Thorax Abdomenmentioning
confidence: 99%